2021
DOI: 10.1097/gme.0000000000001805
|View full text |Cite
|
Sign up to set email alerts
|

Symptom experience during the late reproductive stage and the menopausal transition: observations from the Women Living Better survey

Abstract: Objective: The aim of this study was to examine the occurrence of a variety of symptoms, their frequency, bother, burden, and interference in the lives of women in the late reproductive stage (LRS) and compare their experiences to that of women in the menopausal transition (MT) stage. Methods: Women ages 35 to 55 years responded to an 82-question online survey offered by Women Living Better. Participants reported current menstrual patterns, recent changes and symptom fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(58 citation statements)
references
References 40 publications
1
55
2
Order By: Relevance
“…In this study, several women in the late reproductive stage also reported the presence of VMS; 15.2% had hot flashes and 11.1% had either night sweats or palpitations. Previous studies have reported night sweats in 40.0% and hot flashes in 29.0% of late reproductive women aged 35-55 years [37]. It is important to note that VMS can begin at earlier stages, such as the late reproductive stage, although in a low proportion due to estrogen reduction through constant aging and death of follicles [38].…”
Section: Discussionmentioning
confidence: 93%
“…In this study, several women in the late reproductive stage also reported the presence of VMS; 15.2% had hot flashes and 11.1% had either night sweats or palpitations. Previous studies have reported night sweats in 40.0% and hot flashes in 29.0% of late reproductive women aged 35-55 years [37]. It is important to note that VMS can begin at earlier stages, such as the late reproductive stage, although in a low proportion due to estrogen reduction through constant aging and death of follicles [38].…”
Section: Discussionmentioning
confidence: 93%
“…In a 2020 WLB survey aimed at creating a better understanding of women's experience during the menopausal transition, participants were queried about 61 symptoms gathered from a variety of sources, that are sometimes associated with the menopause transition. Only two symptoms, vaginal pain in the absence of sex (3%) and more interest in sex (9%) were reported by fewer than 10% of women, all others were reported by more than 10% of people surveyed [1]. Most people associate the menopausal…”
Section: A Broader Range Of Symptoms Than Commonly Recognizedmentioning
confidence: 98%
“…When asked to think back to when they were 30 about at what age they assumed changes associated with the menopause transition would begin, 59% of women anticipated changes at 50 or later and another 28% said 45-49 years old. Only 13% assumed changes would begin before age 44 [1]. Because they haven't been given anticipatory guidance to expect changes in their late 30s or early 40s as ovarian follicles significantly decline and reproductive hormone patterns change, when the first changes occur, most don't know what is happening to them or within their bodies.…”
Section: Lack Of Education Leads To Misattribution Confusion and Fearmentioning
confidence: 99%
See 2 more Smart Citations